Analisis Bayangan Dalam Macbeth Karya William Shakespeare - Tuti Handayani; Syahrul Ramadhan; Siti Armelia Hamidah (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2024)
Macbeth was one of William Shakespeare's famous plays that used many shadows to beckon events to come in this story. In Macbeth's stories shadows are used to create tensions and raise questions about agency and moral responsibility in the drama. This study aims to analyze and identify the use of additives in the text and connect it to the development of themes and characters in Macbeth's story. In addition, the researchers also used interpretation and evaluation. After evaluating "Macbeth," the researcher gives his own view of the work. This data-research method employs a qualitative approach. Research shows that parallels are used in "Macbeth" to predict the direction of the story, build tensions, and develop character. Parallels are used to show changes in character and awareness of responsibility dealt with by Macbeth. Examples of vocations used in "Macbeth" include witch prophecies, soliloquy Macbeth, hallucinations and visions, and the use of invention. These barriers help build tensions and predict the tragic end of the main character